Desterritorializar e reterritorializar: jornais regionais gaúchos e estratégias de aproximação com os leitores - Sparremberger, Fabiana (2018)
This research analyzes the strategies employed by gaucho regional newspapers to reach out its readers. The theoretical framework of this research is a coupling between Luhmann‟s social systems theory (1997, 2005, 2010) and the concepts of mediatization, from the approaches of Verón (2012), Braga (2006), Fausto Neto (2006), and discourse, from the semiological perspectives of Verón (2004), Orlandi (2001) and Foucault (2008). To investigate how regional newspapers develop discursive strategies to approach its readers in a time in which they seek the preservation of the market, the research was developed - from the embedded multiple case study (YIN, 2001) led by the evidentiary paradigm – in the following newspapers: Pioneiro, from Caxias do Sul, and Gazeta do Sul, from Santa Cruz do Sul. There are three theoretical and methodological procedurals linked to specific research objectives. The first one, used to define the corpus involved simple observation (GIL, 2008) in the regional newspaper websites to identify the strategies, relating recurring and unique divergent and convergent aspects. Then, through in-depth interviews (DUARTE, 2006) with the eight directors and managers of the two newspapers, the parameters used to select the strategies to approach the readers were - that go beyond journalistic content - and its impacts, whether economic or maintenance of own journalistic system. The last step was to identify how strategies are set out from market, organizational, economic and political logics, analyzing the reading contracts (VERÓN, 2004) and the discursive marks led by readers (2004). It was noted that regional newspapers enunciate the triad of goals they pursue in search of preservation as autopoietic social systems (LUHMANN, 1997, 2005, 2010): quality content; territorial repossession strategies (HAESBAERT, 2007, 2014) who try engagement with readers through market and organizational actions; and territorial dispossession strategies (HAESBAERT, 2007, 2014), focusing on digital profitability. However, from the research emerged questions still unanswered: Larger investments in territorial repossession strategies are sufficient to ensure the maintenance of regional newspapers? How does the non- consideration of the discursive circulation as a real threat to the system interferes on its survival? And the extents to which cultural and economic systems determine the preservation of the regional newspaper?